THE BEAUTY PROPAGANDA IN BODY CARE ADVERTISEMENTS - Finda Muftihatun Najihah (PARADIGM: Journal of Language and Literary Studies, 2020)
This study investigates the application of Critical Discourse Analysis to the body care advertisements. In this study, the focus is on the discourse and the text of advertisement which create the ideological concept of beauty. The theory used is Fairclough’s three dimensional framework which concentrates on the textual features, discursive practice, and discourse as social practice. The discourses of body care advertisements which are analyzed are from three brands; Oriflame, Wardah and Nivea. Methodologically, descriptive qualitative is used in this study as the research design because the purpose of this study is to provide a deep analysis of the data. The findings reveal that the use of adjectives has two main functions, to describe the product and to describe the result after using the product. In addition, the presence of the verbs has function to describe the work and the quality of the products advertised. Furthermore, the most pronouns used in the advertisements is “your” which has function to directly point at the reader so the reader will fell engaged to the advertisement. In discursive techniques the finding shows there are nine techniques used to promote the products advertised. They are using natural resources ingredients or by giving clinical test proof, exposure of the existing content, self-representations, unrealistic representations through the exaggeration language, puffery which contain the discourse which is subjective without giving credible evidence, the use of emotive words, celebrity endorsement, the simple discourse used and the last is by offering discount sale on the product advertised. It is also found that the ideological concept of beauty is emerged by the limitation of the concept beauty on the discourse and image of beauty advertisements. The concept of beauty is divided into 3, the concept of eyes, ideal skin, and ideal lip.